Optimization of protease extraction and characterization of protease from syzygium polyanthum as potential meat tenderizer - Noorhafiza, Yahya (2023)
Meat tenderness is a crucial trait that contributes to the consumer eating satisfaction and acceptance in meat product marketability. Therefore, an effective meat tenderization technique is required by exploring plant-based protease as meat tenderizer. In spite of easy availability of commercial meat tenderizer including bromelain and papain, Syzygium polyanthum leaves have not been explored by the meat industry due to lack of scientific literature. Besides, the concentration of components used in the extraction buffer during the extraction of protease from the leaves of S. polyanthum have not been optimized. Hence, a 24 full factorial design (FFD) was performed to screen the concentration of potassium phosphate (KPO4), Triton X-100, glycerol and dithiotreitol (DTT) in the extraction buffer that affect the protease activity. The results demonstrated that the concentration of KPO4 and DTT contributed significantly to the effect of protease activity. Later, the extraction of protease was optimized using response surface methodology (RSM) by varying the concentration of KPO4 and DTT in the extraction buffer. The results showed that the extraction buffer formed by 3.18 M of KPO4 and 1.81 M of DTT exhibited the optimal protease activity with R2 of 0.8357. There was no significant difference (0.082 %) between the predicted (0.5004 U/ mL) and experimental results (0.5008 ± 0.0500 U/ mL). The optimum temperature and pH for the protease activity of S. polyanthum protease were found to be at 60 °C and pH 7. The S. polyanthum protease was identified as cysteine protease because it was inhibited by iodoacetamide, a cysteine protease inhibitor. In the present study, the S. polyanthum protease exhibited comparable ability with papain as meat tenderizer at different unit activity (U/ mL) by showing a reduction in a number of protein bands in the electrophoretic analysis. There were an increase of water holding capacity (WHC) and a decline of pH with the increase of protease activity for both proteases (S. polyanthum protease and papain). These results conclude that S. polyanthum protease can be employed as a potential alternative meat tenderizer.